Molds of Their Homeland: Symbols of Identity in the Works of Asam Abu Shakra and Tsibi Geve - Yacobi, Haim (Hagar: Studies in Society and Culture, 2000)
Art exhibition, Ben Gurion University Library, May-July 2000